What is history? - Carr, Edward Hallett, 1892- (New York : Vintage, 1967)
Discusses how people determine what history is and explains why certain events are remembered and included in historical study and others are not.
"The George Macaulay Trevelyan Lectures delivered at the University of Cambridge, January-March 1961.".
Adult
Keywords: History -- Philosophy; History -- Philosophy